Prediction of Future Rainfall using SDSM at Catchment Bukit Merah - Abdul Hamid, Amylira; Abdullah, Nor Maizzaty; Hamidon, Nuramidah (Progress in Engineering Application and Technology, 2022)
From decades to millennia, climate change is a shift in the statistical distribution of weather patterns. Climate change may alter the mean weather conditions, as well as the frequency and duration of weather fluctuations, more or fewer extreme weather conditions such as floods and droughts. Climate change directly affects natural resource depletion, infrastructure, the environment, and human health. Also, certain indirect consequences may be severe. The primary goal is to investigate and establish the use of the Statistical DownScaling Model (SDSM) in predicting the future and precipitation of a specific catchment area in peninsular Malaysia by downscaling the current climate change from 2010 to 2021 and future climate variables for the Bukit Merah basin, and also to predict the rainfall impact of climate change on the Bukit Merah reservoir from 2022 to 2050. Bukit Merah watershed has its own reservoir (BMR). It is also known as Bukit Merah Lake. Freshwater lakes and reservoirs provide water for home use, irrigation, agriculture, and industry. Thus, this study will use statistical downscaling to predict future rainfall in the catchment Bukit Merah by Statistical Downscaling Method (SDSM). From this study, the outcome result indicated Bukit Larut has the highest mean rainfall while Bukit Merah has the lowest mean rainfall in 30 years later.